Prognostic Values of Platelet-Associated Indicators in Resectable Lung Cancers. (14th March 2019) - Wang, Jing-Jing; Wang, Yin-Ling; Ge, Xin-Xin; Xu, Meng-Dan; Chen, Kai; Wu, Meng-Yao; Gong, Fei-Ran; Tao, Min; Wang, Wen-Jie; Shou, Liu-Mei; Li, Wei
Background: Lung cancer is the leading cause of cancer death. Platelet-related indictors, including platelet count, plateletcrit, mean platelet volume, and platelet distribution width, not only associate with morphology and functions of platelet but also correlate with tumor development and metastasis. In the present study, we investigated the values of platelet-related indictors in the prognosis evaluation of resectable lung cancers. Methods: In total, 101 patients with resectable lung cancer were recruited in this study. Patients were divided into 2 groups according to the median pretreatment values. To evaluate the individual value changes after treatment, we introduced the concept of post-/pretreatment ratio (≤1 indicated value was not increased after treatment, while >1 suggested increased value). Results: The high pretreatment platelet count level was correlated with larger tumor size. High pretreatment plateletcrit level was associated with more lymph nodes metastasis. Patients with high pretreatment plateletcrit level had worse overall survival, whereas pretreatment platelet count, mean platelet volume, and platelet distribution width levels were not correlated with outcomes. Surgery had no impact on the values of platelet count, plateletcrit, mean platelet volume, or platelet distribution width. Adjuvant chemotherapy significantly decreased the values of platelet count and plateletcrit, whereas it had no effect on the values of mean platelet volume or platelet distribution width. Whole course of treatment (surgery combined with adjuvant chemotherapy) significantly decreased the values of platelet count and platelet distribution width, whereas it had no effect on the values of plateletcrit or mean platelet volume. Post-/pretreatment platelet count, plateletcrit, mean platelet volume, and platelet distribution width ratios were not correlated with outcomes. Univariate analyses demonstrated that American Joint Committee on Cancer stage and pretreatment plateletcrit level were significant risk factors for prognosis. Cox regression analysis revealed that no factor independently associated with worse survival. Conclusion: Pretreatment plateletcrit level could be a potential prognostic factor in resectable lung cancers.